Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics